Associations between Interpersonal Behaviour, Cultural Background, Achievement and Engagement in New Zealand Tertiary Blended Learning Environments: A Case Study - Pillay, Nadarajan Sivalingam (Curtin University, 2024)
Using a mixed-methods case study, this thesis explores student and teacher perceptions of blended learning at a New Zealand Institute of Technology. It highlights positive student perceptions of achievement and engagement and recommends improved online support for students. Gender and cultural differences in student perceptions are identified. As blended learning becomes commonplace in higher education, this study helps stakeholders understand the challenges in designing, developing, delivering, and evaluating blended learning programmes for better student outcomes.